2013
DOI: 10.1007/s10067-013-2239-x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in psoriatic arthritis

Abstract: Autonomic nervous system (ANS) involvement has been studied in systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, Sjogren's syndrome, and ankylosing spondylitis but still has not been studied in psoriatic arthritis (PsA). The aim of this study was to investigate the prevalence and the nature of autonomic neuropathy in patients with PsA. Sixteen patients of PsA and 15 age and sex matched control subjects were studied prospectively using a battery of noninvasive tests. Cardiovascular autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…This suggests that these may predict the occurrence of neuropathy and response to treatment. Earlier study on autonomic neuropathy in PsA patients has shown a positive correlation between biomarkers of inflammation (ESR and CRP) and parasympathetic dysfunction [Syngle et al 2013]. In another spondyloarthropathy disease, AS, there is a positive correlation between parasympathetic dysfunction and disease activity (BASDAI) and biomarkers of inflammation (ESR and CRP) [Toussirot et al 1999].…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that these may predict the occurrence of neuropathy and response to treatment. Earlier study on autonomic neuropathy in PsA patients has shown a positive correlation between biomarkers of inflammation (ESR and CRP) and parasympathetic dysfunction [Syngle et al 2013]. In another spondyloarthropathy disease, AS, there is a positive correlation between parasympathetic dysfunction and disease activity (BASDAI) and biomarkers of inflammation (ESR and CRP) [Toussirot et al 1999].…”
Section: Discussionmentioning
confidence: 97%
“…Baseline N=52 Background: Evaluating psoriatic arthritis (PsA)-related enthesitis is diagnostically and therapeutically essential, but may be very complex because of the wide range of signs and symptoms that partly overlap or co-exist with the clinical features of fibromyalgia (FM) [1,2]. Objectives: The primary aim was to compare the prevalence of clinical and ultrasonographic signs of enthesitis in patients with PsA, FM, or both.…”
Section: Variablementioning
confidence: 99%
“…The disease can have a diverse clinical course but usually, manifests as oligoarthritis [1]. Peripheral sympathetic autonomic dysfunction in psoriatic arthritis is known [2]. Secukinumab is an IgG1k fully monoclonal antibody selectively targeting interleukin-17A.…”
Section: Introductionmentioning
confidence: 99%